Preparation of thickness-tunable BiOCl nanosheets with high photocatalytic activity for photoreduction of CO2. Issue 121 (23rd November 2015) - Jin, Jiarui; Wang, Yanjie; He, Tao
Abstract : BiOCl nanosheets with different percentages of exposed {001} facets were prepared via mild hydrolysis by a controlled facile hot injection technique, which exhibited relatively high activity for photocatalytic reduction of CO2 to CH4 . Abstract : BiOCl nanosheets with different percentages of exposed {001} facets were prepared by a controlled facile hot-injection technique. The synthesis was conducted using bismuth chloride as a metal precursor, octadecene as a solvent, and oleic acid, oleylamine and octadecene as morphology-control agents. The presence of trace amounts of water in the reaction system leads to mild hydrolysis. The obtained BiOCl nanosheets with highly exposed {001} facets exhibited high activity for photocatalytic reduction of CO2 to CH4 . Moreover, the thinner the nanosheets, the higher the production yield. The detailed mechanism has been studied. This work may afford a feasible protocol for the preparation of BiOCl nanosheets with high photocatalytic activity.